Genome sequence and analysis of the tuber crop potato - Xu, Xun; Pan, Shengkai; Cheng, Shifeng; Zhang, Bo; Mu, Desheng; Ni, Peixiang; Zhang, Gengyun; Yang, Shuang; Li, Ruiqiang; Wang, Jun; Orjeda, Gisella; Guzman, Frank; et al. (Nature (London), 2011)
Potato ( Solanum tuberosum L.) is the world’s most important non-grain food crop and is central to global food security. It is clonally propagated, highly heterozygous, autotetraploid, and suffers acute inbreeding depression. Here we use a homozygous doubled-monoploid potato clone to sequence and assemble 86% of the 844-megabase genome. We predict 39,031 protein-coding genes and present evidence for at least two genome duplication events indicative of a palaeopolyploid origin. As the first genome sequence of an asterid, the potato genome reveals 2,642 genes specific to this large angiosperm clade. We also sequenced a heterozygous diploid clone and show that gene presence/absence variants and other potentially deleterious mutations occur frequently and are a likely cause of inbreeding depression. Gene family expansion, tissue-specific expression and recruitment of genes to new pathways contributed to the evolution of tuber development. The potato genome sequence provides a platform for genetic improvement of this vital crop. The potato genome The genome of the potato ( Solanum tuberosum L.), a staple crop vital to food security, has been sequenced. The Potato Genome Sequencing Consortium sequenced a homozygous doubled-monoploid potato clone as well as a heterozygous diploid clone. Genome analysis reveals traces of at least two genome duplication events and genes specific to Asterids, a large clade of flowering plants of which the potato is the first to be sequenced. Gene presence/absence variants and other potentially deleterious mutations are frequent and may be the cause of inbreeding depression. The genome sequence will facilitate genetic improvements in the potato with a view to improving yield and to increasing disease and stress resistance of this crop, which is a now a significant component of worldwide food production and is becoming increasingly important in the developing world.